Hospital-associated disability and hospitalization costs for acute heart failure stratified by body mass index- insight from the JROAD/JROAD-DPC database. (15th November 2022) - Ogawa, Masato; Yoshida, Naofumi; Nakai, Michikazu; Kanaoka, Koshiro; Sumita, Yoko; Kanejima, Yuji; Emoto, Takuo; Saito, Yoshihiro; Yamamoto, Hiroyuki; Sakai, Yoshitada; Hirota, Yushi; Ogawa, Wataru; et al.
Abstract: Background: The impact of body mass index (BMI) on hospital mortality in patients with acute heart failure has been well documented in Asian populations. However, the relationship between BMI, hospital-associated disability (HAD), and hospitalization costs in patients with heart failure is poorly understood. This study aimed to explore the impact of BMI on HAD and hospitalization costs for acute heart failure in Japan. Methods: From April 2012 to March 2020, the Japanese Registry of All Cardiac and Vascular Disease Diagnosis Procedure Combination (JROAD-DPC) database was used to identify patients with acute heart failure. All patients were categorized into five groups according to the World Health Organization Asian BMI criteria. The hospitalization costs and HAD were evaluated. Results: Among the 238, 160 eligible patients, 15.7% were underweight, 42.2% were normal, 16.7% were overweight, 19.3% were obese I, and 6.0% were obese II, according to BMI. The prevalence of HAD was 7.43% in the total cohort, and the risk of HAD increased with a lower BMI. Restricted cubic spline analysis showed a U-shaped relationship between BMI and hospitalization costs for all ages. Furthermore, developing HAD was associated with greater costs compared with non-HAD, regardless of BMI category. Conclusions: We found that the lower the BMI, the higher the incidence of HAD. A U-shaped association was confirmed between BMI and hospitalization costs, indicating that hospitalization costs increased for both lower and higher BMI regardless of age. BMI could be an important and informative risk stratification tool for functional outcomes and economic burdens. Graphical abstract: Unlabelled Image Highlights: This study revealed that the prevalence of HAD was 7.43% in heart failure patients. The risk of HAD increased in proportion to thinness. A U-shaped relationship was found between BMI and hospitalization costs at all ages. BMI is a risk stratification tool for functional outcomes and economic burdens.